Burden of disease due to cutaneous melanoma has increased in the Netherlands since 1991. (13th August 2013) - Holterhues, C.; Hollestein, L.M.; Nijsten, T.; Koomen, E.R.; Nusselder, W.; de, E.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Melanoma leads to a loss of 20 years of life during a lifetime. What does this study add? Both the fatal and nonfatal burden of melanoma are important to describe the impact on society, because patients live on average 19–27 years with melanoma. The burden of melanoma has increased rapidly, now exceeding 21 000 disability‐adjusted life‐years annually. There is a general need for an empirical estimation of disability weights and duration of disease.